2014
DOI: 10.3928/01477447-20140924-04
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Fixation of Anterior and Posterior Column Acetabular Fractures

Abstract: Although open reduction and internal fixation (ORIF) has been the standard of care for acetabular fractures, recent advancements in minimally invasive techniques have allowed percutaneous fixation to gain popularity. Percutaneous technique has been described in the literature as an adjuvant to ORIF. However, isolated percutaneous fixation has the advantage of limiting soft tissue disruption, length of surgery, and blood loss when compared with ORIF. The technique also allows for earlier return to activity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 11 publications
(14 reference statements)
0
7
0
1
Order By: Relevance
“…reported that percutaneous fixation of anterior and posterior column acetabular fractures has the advantage of limiting soft tissue disruption, length of surgery and blood loss when compared with ORIF. 24 We believe that percutaneous fixation of anterior column, when combined with modified K-L approach for fixation of complex acetabular fractures, shall provide anatomical reduction and also reduce operative time, blood loss and prevent complications associated with open reduction techniques.…”
Section: Discussionmentioning
confidence: 99%
“…reported that percutaneous fixation of anterior and posterior column acetabular fractures has the advantage of limiting soft tissue disruption, length of surgery and blood loss when compared with ORIF. 24 We believe that percutaneous fixation of anterior column, when combined with modified K-L approach for fixation of complex acetabular fractures, shall provide anatomical reduction and also reduce operative time, blood loss and prevent complications associated with open reduction techniques.…”
Section: Discussionmentioning
confidence: 99%
“…tas, que complicaría o evitaría las técnicas abiertas. [5][6][7] • Se puede usar como complemento en la reducción abierta en patrones complejos de fracturas. 6,7 Las complicaciones de la fijación pélvica percutánea son variadas y se dividen en errores relacionados con el cirujano, la técnica y el paciente.…”
Section: Level Of Evidence: IVunclassified
“…Open reduction and internal fixation is considered the gold standard of treatment, especially in displaced fractures involving the weight-bearing surface or the posterior wall. For acetabular fractures in the elderly as well as less-or undisplaced fractures in patients aiming for an early return activity, percutaneous techniques with cannulated screws [36] or minimally invasive plate osteosynthesis (MIPO) using preshaped 3D plates [37] are on a rise. Although long-term outcomes are limited, most advanced treatment methods including minimally invasive fixation under computer-assisted navigation [38] and 3D printing, simulating the plate preflex and screw length [39], are promising to improve surgical accuracy and safety and to shorten the operation time.…”
Section: Pelvismentioning
confidence: 99%